2022
DOI: 10.3390/su14137730
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Digital Leadership in School Management and Accessibility of Animation-Designed Game-Based Learning for Sustainability of Education for Children with Special Needs

Abstract: With the rapid integration of technology into educational environments during the pandemic period, the teaching processes in classrooms and private education institutions began to be carried out with technology support. Game-based animation learning designs in technology-supported educational environments provide an interesting and motivation-enhancing learning experience in developing students’ education skills. In today’s educational environments, 2D and 3D animation game designs are the unique technology-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Cluster 3 Hypothesis: The level of digital innovation within an organization positively influences leadership practices and contributes to sustainable performance outcomes. Helpful resources for building this hypothesis are Mollah et al (2023), Shin et al (2023), Quaquebeke and Gerpott (2023), Karakose and Tülübaş (2023), Zulu et al (2023), Karakose et al (2022), Niu et al (2022), Khaw, et al (2022), Erhan et al (2022), Baglama et al (2022), andBenitez et al (2022).…”
Section: Formulating Hypotheses From Clusters For Building a Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Cluster 3 Hypothesis: The level of digital innovation within an organization positively influences leadership practices and contributes to sustainable performance outcomes. Helpful resources for building this hypothesis are Mollah et al (2023), Shin et al (2023), Quaquebeke and Gerpott (2023), Karakose and Tülübaş (2023), Zulu et al (2023), Karakose et al (2022), Niu et al (2022), Khaw, et al (2022), Erhan et al (2022), Baglama et al (2022), andBenitez et al (2022).…”
Section: Formulating Hypotheses From Clusters For Building a Modelmentioning
confidence: 99%
“…Globalization has led to a rapid acceleration of changes, particularly in the realm of technology, where significant advancements have been witnessed. Leadership models have also transformed and adapted to keep pace with the evolving landscape (Baglama et al, 2022). As organizations strive to adapt to the evolving digital landscape, effective leadership becomes critical in navigating through these changes successfully.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of sustainability is intrinsically related to educational issues, and different studies have focused on demonstrating such inter-association, whether in environmental aspects, e.g., [23][24][25], in social aspects [26][27][28], or in topics related to corporate governance, e.g., [5,7,29]. Considering the focus of this work, we focused on elaborating a non-exhaustive review of works that have demonstrated the importance of formally and systematically incorporating the in-depth study of the discipline of corporate governance into business courses, so that students can infer the importance of ethical attributes in business decision making, and that take into account the environmental and social dimensions that are affected by organizational initiatives.…”
Section: Corporate Governance For Business Students and Sustainabilitymentioning
confidence: 99%
“…Companies in all industries are increasingly digitized and form digital organizations, and digital transformation is a fast-changing business widely for which companies lag behind in the digitization process; companies will become slower, less flexible, and even lag behind competing companies compared to digital pioneer companies. Facing change is certainly not an Several previous studies have examined digital leadership (Alshehab et al, 2022;Amelda et al, 2021;Baglama et al, 2022;Ehlers, 2020;Gierlich-Joas et al, 2020;Jagadisen et al, 2022;Jesse, 2018;Kane et al, 2019;Karakose et al, 2022;McGillivray et al, 2016;Leonardus W.W. Mihardjo et al, 2019;Leonardus W.Wasono Mihardjo et al, 2019;Niu et al, 2022;Peter et al, 2020;Robertson et al, 2022;Sasmoko et al, 2019;Furinto, 2018;Yopan et al, 2022;Yusof et al, 2019;Zulu &;Khosrowshahi, 2021). For example, Schiuma et al (2022) examine digital leadership in terms of transformative leadership profiles that support the development of corporate digital transformation.…”
Section: Introductionmentioning
confidence: 99%